2014
DOI: 10.4238/2014.june.11.4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of diversity and relationships among orchardgrass (Dactylis glomerata L.) accessions using start codon-targeted markers

Qi X2,
et al.

Abstract: ABSTRACT. Orchardgrass, or cocksfoot, is an important perennial forage grass worldwide. The comprehensive understanding of orchardgrass accessions will benefit germplasm collection and breeding progress, and it will enhance efforts to improve forage yield and quality. Therefore, 24 novel, simple, polymorphic, and reliable start codon-targeted (SCoT) markers were used to analyze the diversity and genetic relationships among 95 orchardgrass accessions. In total, 273 polymorphic bands were detected with an averag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 33 publications
1
11
0
2
Order By: Relevance
“…SCoT markers were used for the first time in E. sibiricus due to several advantages to other marker techniques: easier development of species-specific primers than SSR [ 22 ], lower cost than AFLP [ 22 ] and higher reproducibility than RAPD [ 18 ]. The results of the present study showed that SCoT markers were efficient in assessing the genetic diversity among E. sibiricus accessions.…”
Section: Resultsmentioning
confidence: 99%
“…SCoT markers were used for the first time in E. sibiricus due to several advantages to other marker techniques: easier development of species-specific primers than SSR [ 22 ], lower cost than AFLP [ 22 ] and higher reproducibility than RAPD [ 18 ]. The results of the present study showed that SCoT markers were efficient in assessing the genetic diversity among E. sibiricus accessions.…”
Section: Resultsmentioning
confidence: 99%
“…Genetic diversity of Dactylis was assessed using a range of protein and DNA markers including allozymes [27,31]; SSR [24,[32][33][34][35] [24,32,33,34,35]; RAPD/ISSR/SCoT [35][36][37][38] [35,36,37,38]; AFLP [38] and SNPs [32]. Nuclear genotyping by sequencing (GBS) was used by Bushman et al [39], but not for genetic diversity studies.…”
Section: Introductionmentioning
confidence: 99%
“…Using 37 SCoT markers we were able to distinguish all 111 genotypes of the ricin. FANG-YONG et al, 2014;JIANG et al, 2014;HUANG et al, 2014;SATYA et al, 2015) and these values presented a high level of polymorphism of genotypes detected by SCoT markers. HUANG et al (2014) assessed the genetic diversity of six Hemarthria cultivars using seven SCoT primers, which together amplified 105 bands with an average of 15 bands per sample.…”
Section: Resultsmentioning
confidence: 93%
“…In principle, SCoT is similar to RAPD and ISSR because the same single primer is used as the forward and reverse primer (COLLARD and MACKILL, 2009). Suitability of SCoT markers system has been successfully employed in genetic diversity analysis and fingerprinting of a number of agricultural and horticultural crop species, such as oat (BALÁŽOVÁ et al, 2017), rye (PETROVIČOVÁ et al, 2017), maize (VIVODÍK et al, 2016, date palm (AL-QURAINY et al, 2015), orchardgrass (JIANG et al, 2014), pepper (TSABALLA et al, 2015, ramie (SATYA et al, 2015), castor (KALLAMADIA et al, 2015), sugarcane (QUE et al, 2014) and mango (GAJERA et al, 2014).…”
Section: Introductionmentioning
confidence: 99%